Association of Carotid Artery Plaque With Cardiovascular Events and Incident Coronary Artery Calcium in Individuals With Absent Coronary Calcification: The MESA. (8th April 2021) - Mehta, Anurag; Rigdon, Joseph; Tattersall, Matthew C.; German, Charles A.; Barringer, Thomas A.; Joshi, Parag H.; Sperling, Laurence S.; Budoff, Matthew J.; Bertoni, Alain; Michos, Erin D.; Blaha, Michael J.; Stein, James H.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Absence of coronary artery calcium (CAC) identifies asymptomatic individuals at low cardiovascular disease risk. Carotid artery plaque is a marker of increased risk, but its association with cardiovascular risk and incident CAC in people without CAC is unclear. Methods: Multi-Ethnic Study of Atherosclerosis participants with CAC score of 0 at enrollment who also underwent carotid plaque measurement using B-mode ultrasonography were prospectively followed for incident coronary heart disease, stroke, and cardiovascular disease events, and CAC (score >0 on up to 3 serial computed tomography scans). The association of carotid plaque presence and plaque score (Ln[score+1]) at baseline with cardiovascular events and incident CAC was evaluated with Cox proportional hazards regression models adjusted for demographics, risk factors, and statin use. Results: Among these 2673 participants (58 years, 64% women, 34% White, 30% Black, 24% Hispanic, and 12% Chinese), carotid plaque at baseline was observed in 973 (36%) and the median plaque score (range, 1–12) among those with plaque was 1. A total of 79 coronary heart disease, 80 stroke, and 151 cardiovascular disease events were observed during 16.1 years of follow-up. Carotid plaque presence and plaque score were independently associated with coronary heart disease risk (HRs, 1.66 [95% CI, 1.04–2.66]; and 1.48 [95% CI, 1.01–2.17], respectively) but not with stroke and cardiovascular disease risk. A total of 973 (36.4%) participants developed CAC over the evaluation period (median 9.3 years). Carotid plaque presence and plaque score were independently associated with incident CAC (HRs, 1.34 [95% CI, 1.18–1.54]; and 1.37 [95% CI, 1.21–1.54]), respectively. Conclusions: The presence and extent of carotid plaque are associated with long-term coronary heart disease risk and incident CAC among middle-aged asymptomatic individuals with an initial CAC score of 0.